Pharmacological inhibition of MAGL attenuates experimental colon carcinogenesis. (May 2017) - Pagano, Ester; Borrelli, Francesca; Orlando, Pierangelo; Romano, Barbara; Monti, Martina; Morbidelli, Lucia; Aviello, Gabriella; Imperatore, Roberta; Capasso, Raffaele; Piscitelli, Fabiana; Buono, Lorena; Di Marzo, Vincenzo; et al.
Graphical abstract: Abstract: Colorectal cancer (CRC) is a major health problem in Western countries. The endocannabinoid 2-arachidonoyl-glycerol (2-AG) exerts antiproliferative actions in a number of tumoral cell lines, including CRC cells. Monoacylglycerol lipase (MAGL), a serine hydrolase that inactivates 2-AG, is highly expressed in aggressive human cancer cells. Here, we investigated the role of MAGL in experimental colon carcinogenesis. The role of MAGL was assessed in vivo by using the xenograft and the azoxymethane models of colon carcinogenesis; MAGL expression was evaluated by RT-PCR and immunohistochemistry; 2-AG levels were measured by liquid chromatography mass spectrometry; angiogenesis was evaluated in tumor tissues [by microvessel counting and by investigating the expression of vascular endothelial growth factor (VEGF) and fibroblast growth factor-2 (FGF-2) proteins] as well as in human umbilical vein endothelial cells (HUVEC); cyclin D1 was evaluated by RT-PCR. MAGL and 2-AG were strongly expressed in tumor tissues. The MAGL inhibitor URB602 reduced xenograft tumor volume, this effect being associated to down-regulation of VEGF and FGF-2, reduction in the number of vessels and down-regulation of cyclin D1. In HUVEC, URB602 exerted a direct antiangiogenic effect by inhibiting FGF-2 induced proliferation and migration, and by modulating pro/anti-angiogenic agents. In experiments aiming at investigating the role of MAGL in chemoprevention, URB602 attenuated azoxymethane-induced preneoplastic lesions, polyps and tumors. MAGL, possibly through modulation of angiogenesis, plays a pivotal role in experimental colon carcinogenesis. Pharmacological inhibition of MAGL could represent an innovative therapeutic approach to reduce colorectal tumor progression.